Efficiency of dexamethasone in reducing the incidence of headaches after spinal anesthesia during caesarean section - Noor Sabri Ali; Sajidah Al-Rubaai; Tishreen Sabri Ali (Romanian Medical Journal)
Background. A caesarean section is the delivery of a fetus through an abdominal incision (laparotomy) and a uterine incision (hysterectomy). The anesthesia method most often used for caesarean birth is spinal anesthesia, the prevailing complication of spinal anesthesia (SA) is post-dural puncture headache. Aims of the study. To investigate the effects of dexamethasone in reducing the incidence of headache and pain in spinal anesthesia in caesarean section. Subjects and methods. Clinical trial was conducted at Basra Maternity and Children Hospital from January 1, 2022 to July 1, 2023. The studied population was divided into two groups: Group I included 98 patients who received intravenous dexamethasone 0.2 mg/kg (maximum 16 mg) just after the spinal anesthesia, and Group II, the control group, which included 100 patients who received IV normal saline prior to spinal anesthesia. The average severity of headache was evaluated using the visual analogue scale (VAS) after recovery within the first hour, 24 hours, 48 hours, and 1 week. Results. Dexamethasone usage significantly reduced postoperative pain (no pain: 89.7% vs. 68.0%), with a p-value equal to 0.001. No notable differences were found in sociodemographic characteristics, PDPH incidence (recovery time: 8.1% vs. 9.0%, 24 hours: 10.2% vs. 9.0%, 48 hours: 4.08% vs. 5.0%, one week: 0.0% vs. 0.0%). Conclusion. Dexamethasone given intravenously had no discernible effect on headaches following a spinal puncture. It dramatically lowers pain after surgery, but it has no discernible impact on bradycardia, nausea or vomiting, shivering, or postoperative hypotension.